Physical, morphological, and mechanical properties of raw and steamed cashew nuts (Anacardium occidentale L.) (2024)
Cashew (Anacardium occidentale L.) plays an important role in global agriculture, particularly in commercializing the cashew kernel. Nevertheless, kernel extraction poses a challenge due to the nut variable shape and size. Characterizing the properties of the cashew nut becomes a pivotal input for the advancement of processes and machinery. This work presents a comprehensive characterization of raw and steamed cashew nuts from Puerto Carreño, Colombia, with focus on morphological, physical, and mechanical properties. Cashew nut samples from different farms in the region were collected. Morphological properties, including size and shape, were analyzed by measuring length, width, and thickness for 100 nuts from each supplier, both in their raw state and after steaming. Geometric diameter and sphericity were calculated, and qualitative shape characterization was performed. Physical properties, such as mass, bulk density, true density, and moisture content, were also measured. Angle of repose and coefficient of friction were determined to assess flow and frictional behavior. Additionally, compressive mechanical properties were evaluated through uniaxial compression testing along three orientations. The findings indicated significant differences in morphological and mechanical properties between raw and steamed cashew nuts. Conversely, the results demonstrated that cashew nuts from Vichada region exhibit a noteworthy degree of dispersion and larger dimensions than those from Asia and Africa, comparable to those from Brazil. The findings guide machinery design in the cashew industry and offer insights into the physical, morphological, and mechanical properties of cashew nuts in Puerto Carreño, contributing to understanding and enabling quality assessment, processing optimization, and product development.